Pengaruh Kepemimpinan Autentik CEO Terhadap Komitmen Afektif dan Symmetrical Internal Communication: Studi pada Perusahan Plywood Temanggung - Chike Amanda Selsa; Harmanda Berima Putra (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This study aims to examine the influence of CEO authentic leadership on symmetrical internal communication and employee affective commitment in the context of a plywood company. This research uses quantitative methods by distributing questionnaires to 190 plywood company workers around Temanggung. The results of analysis using regression analysis show that authentic leadership has a positive effect on affective commitment and symmetrical internal communication in the context of plywood companies in Temanggung.